Pengaruh Labelisasi Halal terhadap Keputusan Pembelian pada Masyarakat Muslim Kabupaten Tulungagung - Prasetyo, Faradella Harum; Anwar, Mochammad Khoirul (Universitas Negeri Surabaya, 2021)
The purpose of this study was to identify the effect of halal labeling on purchasing decisions for bottled drinking water products in the Muslim community of Tulungagung Regency. This study uses a quantitative approach. The variables used are halal labeling as the independent variable (X) and purchasing decisions as the dependent variable (Y). The population used was the Muslim community of Tulungagung Regency with the sampling technique using purposive sampling then the population was calculated using the Slovin formula to determine the number of samples. The data used are primary data with data collection techniques through online questionnaires using google form media then distributed with social media WhatsApp and Instagram. Respondents' answers were measured using a Likert scale. The goodness of the questionnaire was tested using validity and reliability tests. This research uses descriptive analysis method and inferential analysis. Inference analysis method used is simple linear regression analysis. The results of this study indicate that halal labeling has a positive and significant effect on purchasing decisions for bottled water products in the Muslim community of Tulungagung Regency. The coefficient of determination (R²) is 0.605 which means that the halal labeling variable has a 60.5% effect on the variable purchasing decisions for bottled drinking water products in the Muslim community of Tulungagung Regency, the rest is influenced by other variables not examined in this study.